Prevalence of metabolic syndrome and its association with risk factors in patients with established atherosclerosis disease - ALINE LONGO; BRUNA L.P. RIBAS; SILVANA P. ORLANDI; BERNARDETE WEBER; EDUARDO G. BERTOLDI; LÚCIA R. BORGES; RENATA T. ABIB (Anais da Academia Brasileira de Ciências)
Abstract Risk factors can lead to clinical conditions, like metabolic syndrome, that predisposes the development of cardiovascular diseases. The aim of this study was to describe the prevalence and which risk factors cause more impact in metabolic syndrome in patients with established atherosclerosis disease. A cross-sectional study was performed as a subanalysis of Programa Alimentação Cardioprotetora Brasileira. Weight, height, waist circumference, blood pressure, lipid profile and fasting glucose were collected. Metabolic syndrome was defined according to the harmonized criteria. Linear regression was used to analyze the association between number of components of metabolic syndrome and risk factors. 82 patients were included and the prevalence of metabolic syndrome was 84.1%. Being overweight was associated with an increase by 0.55 point in diagnostic criteria of metabolic syndrome in crude analysis (95%CI 0.09-1.00) and 0.64 in adjusted analysis (95%CI 0.18-1.09), while former/current smoker status was responsible for raising by 0.48 the number of components of metabolic syndrome, only in adjusted analysis (95%CI 0.04-0.92). Overweight and former/current smoker status are associated with MS, increasing the probability of atherosclerotic events. A healthy lifestyle, that includes avoiding tobacco exposure and proper weight control, must be encouraged in this high-risk population.